Care of the Patient with Anorectal Trauma - Herzig, Daniel O. (Clinics in Colon and Rectal Surgery, 2012)
Blunt and penetrating injuries to the anus and rectum are uncommon. Considerable debate remains regarding the optimal treatment of rectal injuries. Although intraperitoneal rectal injuries can be treated similarly to colonic injuries, treatment options for extraperitoneal injuries include fecal diversion with a colostomy, presacral drainage, repair of the rectal defect, and distal rectal washout. Perineal injuries resulting in anal sphincter disruption often occur with severe associated injuries. Small defects can be repaired primarily, but extensive injuries often require diversion and sphincter reconstruction.
Keywords: anus; rectum; trauma; anorectal trauma; extraperitoneal rectal trauma; anal sphincter trauma